PANTI WERDHA DI BANJARBARU - Ramadini, Ratu Lukitasari; Oktaviana, Anna (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Panti Werdha in Banjarbaru is a community service institution managed by the private sector with the aim of promoting the tranquility of the elderly in their old age. The lack of availability of supporting facilities in Banjarbaru has led to a decrease in peer attention to the elderly in Banjarbaru. The hope is that the design of the Nursing Home in Banjarbaru will be able to improve the quality of life for the elderly in Banjarbaru. The problem that the author raises in the design of social services for the elderly is, How is the design of the elderly housing in Banjarbaru that can facilitate comfortable and safe activities for the elderly? The method that the author applies in solving this problem is the Person Centered Map, using the concept of Behavioral Architecture.